Crossover trial to test the acceptability of a locally produced lipid-based nutrient supplement (LNS) for children under 2 years in Cambodia: a study protocol. Issue 9 (6th September 2017) - Borg, Bindi; Mihrshahi, Seema; Griffin, Mark; Chamnan, Chhoun; Laillou, Arnaud; Wieringa, Frank T
Abstract : Introduction: The acceptability and efficacy of existing ready-to-use supplementary and therapeutic foods has been low in Cambodia, thus limiting success in preventing and treating malnutrition among Cambodian children. In that context, UNICEF and IRD have developed a locally produced, multiple micronutrient fortified lipid-based nutrient supplement. This food is innovative, in that it uses fish instead of milk as the animal source food. Very few supplementary foods have non-milk animal source foods, and in addition they have not been widely tested. This trial will assess the novel food's acceptability to children and caregivers. Methods and analysis: This is a cluster-randomised, incomplete block, 4×4 crossover design with no blinding. It will take place in four sites in a community setting in periurban Phnom Penh. Healthy children aged 9–23 months (n=100) will eat each of four foods for 3 days at a time. The amount they consume will be measured, and at the end of each 3-day set, caregivers will assess how well their child liked the food. After 12 days, caregivers themselves will do a sensory test of the 4 foods and will rank them in terms of preference. Ethics and dissemination: Ethical clearance was received from the University of Queensland Medical Research Ethics Committee (2014001070) and from Cambodia's National Ethics Committee for Health Research (03/8 NECHR). Registration: ClinicalTrials.gov, identifier: LNS-CAMB-INFANTS; NCT02257437 . Pre-results.